Unveiling the dynamics of the business sustainability model: a holistic analysis of financial and digital transformation - Indra Siswanti; Hosam Alden Riyadh; Yohanes Ferry Cahaya; Yananto Mihadi Putra; Baligh Ali Hasan Beshr (Cogent Business & Management, 2024)
The paper introduces a new model that reveals multifaceted financial factors impacting the sustainability of Islamic rural banks, including financing quality, capital quality, financial performance, and digital transformation. Among these, several financial-influencing aspects are associated with business sustainability. The research objectives, thus, are to investigate, first, the impact of financing quality and the quality of capital on business sustainability; second, the impact of financing quality and the quality of capital on financial performance; third, financial performance in mediating the effect of financing quality and capital quality on business sustainability; and fourth, digital transformation in moderating the effect of financial performance on business sustainability. The study employed quantitative research methods, utilizing data from 164 Islamic rural banks' financial and annual reports for the 2016–2021 period. The authors then conducted the analysis using partial least squares (PLS). The research findings unveiled that financing and capital quality exerted an impact on sustainable businesses. Furthermore, financing and capital quality had a significant impact on Islamic rural banks' financial performance. The study also uncovered that financial performance completely mediated the impact of financing quality on the sustainability of Islamic rural banks. On the other hand, financial performance was partially showcased to mediate the impact of capital quality on a business's sustainability. In addition, digital transformation moderated the effect of financial performance on the sustainability business of Islamic rural banks.
Keywords: G21; G32; 650; Business sustainability; capital quality; digital transformation; financial performance; financing quality